Entrepreneur Orientation as a Competitive Advantage in Student Business Startups - Mere, Klemens; Sungkawati, Endang; Nur Savitri, Hilda (Publisher Cv. Inara, 2023)
This study aims to describe how the entrepreneurial orientation of students who do startup business has a competitive advantage. This study used a qualitative approach, with student informants doing business startups. Information obtained from interviews and observations. The results of this study indicate that entrepreneurial orientation is demonstrated by the ability to always be innovative, act proactively, and take risks. To have competitive capabilities can be demonstrated through competitive products and prices compared to its competitors. If a startup business wants to have a competitive advantage, it can be created through innovative, proactive, and risk-taking activities.